2012
DOI: 10.1007/s13224-011-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalance of Pregnancy Associated Asymptomatic Bacteriuria: A Study Done in a Tertiary Care Hospital

Abstract: Objectives A prospective study was conducted in the Department of microbiology (IGMC) and the Department of obstetrics & gynecology (KNH), Shimla, and Himachal Pradesh over a period of 1 year from May 2005 to April 2006 on 463 asymptomatic pregnant females with a period of gestation (POG) 28 weeks or less. The aim was to find out the prevalence of pregnancy associated bacteriuria and bacterial causes responsible for this entity. Methods The pregnant women were taught to collect the urine sample by aseptic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 4 publications
10
47
1
1
Order By: Relevance
“…Those women who show positive cultures should be treated as per antimicrobial sensitivity patterns of the bacteria which are isolated from their samples, to prevent maternal and foetal morbidities. In this study, the prevalence of asymptomatic bacteriuria was 7.3%, which was similar to those seen in various other studies [2,[9][10][11][12][13][14]. Neupane et al, (26%) and Imade et al, (45.3%) reported a higher prevalence [15,16].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Those women who show positive cultures should be treated as per antimicrobial sensitivity patterns of the bacteria which are isolated from their samples, to prevent maternal and foetal morbidities. In this study, the prevalence of asymptomatic bacteriuria was 7.3%, which was similar to those seen in various other studies [2,[9][10][11][12][13][14]. Neupane et al, (26%) and Imade et al, (45.3%) reported a higher prevalence [15,16].…”
Section: Resultssupporting
confidence: 90%
“…Different studies done by Chandel et al, [11], Enayat et al, [12], Obirikorang et al, [13], Imade et al, [16], Khattak et al, [22], Jain et al, [23], as significant and insignificant according to the standard criteria. The organisms were identified by routine methods from the samples which showed significant bacteriuria.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli being a commensal of the intestine has common access through the faecal material into the female urinary tract. In this study, it was 44.26% which is on par with findings of Chandel et al, Khattak et al, Jain et al [20][21][22] All the gram-negative isolates of this study exhibited 100% sensitivity to Imipenem and meropenem. Moderate sensitivity was noted to amikacin, cefepime, and amoxyclavulanic acid.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings agree with earlier studies where E. coli was found to be commonest isolate. 2 A number of observational studies have demonstrated the relationship between maternal symptomatic UTI and the risk of PTL and LBW but some of the studies failed to establish the association. 22,23 However, the association of ASB with maternal and foetal complications remains an area of continued debate.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of ASB in pregnant women varies from 4% to 23.9% globally and the higher prevalence is attributed to lack of personal and environmental hygiene, socio-economic status, parity and ABSTRACT Background: The pregnant women are more commonly affected with asymptomatic bacteriuria (ASB) than nonpregnant women and its progression could lead to adverse maternal and perinatal outcomes. The study was designed with an aim to know the prevalence of ASB and its effects on maternal and perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%